2021
DOI: 10.1186/s12870-021-03085-4
|View full text |Cite
|
Sign up to set email alerts
|

Anther dehiscence is regulated by gibberellic acid in yellow lupine (Lupinus luteus L.)

Abstract: Background Anther dehiscence resulting in the release of pollen grains is tightly regulated in a spatiotemporal manner by various factors. In yellow lupine (Lupinus luteus L.), a species that shows cleistogamy, the anthers split before the flowers open, but the course and regulation of this process are unknown. The specific control of anther development takes place via hormonal pathways, the wide action of which ensures reproductive success. In our previous research concerning flower and early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…Indeed, both the jasmonates-related repressor proteins JASMONATE ZIM-DOMAIN (JAZ) and DELLA act synergistically to repress filament development [ 153 ]. The SWOLLEN ANTHER WALL 1 ( SAW1 ) zinc-finger TF enhances GA20ox3 expression in rice promoting microspore and anther development and dehiscence through GAMYB , while the same GAMYB gene is the target of miRNA159 in yellow lupin controlling pollen release [ 154 , 155 ]. In the presence of GA and jasmonates, MYC2 induces TERPENE SYNTHASE genes TPS11 and TPS21 , permitting the emission of volatile sesquiterpenes necessary for flower development [ 156 ].…”
Section: Reproductive Developmentmentioning
confidence: 99%
“…Indeed, both the jasmonates-related repressor proteins JASMONATE ZIM-DOMAIN (JAZ) and DELLA act synergistically to repress filament development [ 153 ]. The SWOLLEN ANTHER WALL 1 ( SAW1 ) zinc-finger TF enhances GA20ox3 expression in rice promoting microspore and anther development and dehiscence through GAMYB , while the same GAMYB gene is the target of miRNA159 in yellow lupin controlling pollen release [ 154 , 155 ]. In the presence of GA and jasmonates, MYC2 induces TERPENE SYNTHASE genes TPS11 and TPS21 , permitting the emission of volatile sesquiterpenes necessary for flower development [ 156 ].…”
Section: Reproductive Developmentmentioning
confidence: 99%
“…JA is thought to play an important role in regulating anther dehiscence (Sanders et al, 2000;Zhao and Ma, 2000;Ishiguro et al, 2001;Scott et al, 2004), and mutations in genes that participate in JA biosynthesis, such as DAD1 and OPR3, cause a similar delay in anther dehiscence (Sanders et al, 1999(Sanders et al, , 2000Stintzi and Browse, 2000;Scott et al, 2004). GA also regulates anther dehiscence in yellow lupine (Lupinus luteus L.) by regulating genes involved in controlling anther structure such as secondary thickening in the endothecium (Marciniak and Przedniczek, 2021). Since we have shown that 35S::OnACS12 can suppress GA levels and upregulate the accumulation of DELLA proteins, the exploration of the relationship between 35S::OnACS12 and JA biosynthesis was necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, genes of the auxin signaling pathway were differentially expressed between fertile and sterile conditions. Marciniak’s results revealed that GA3 contributed to the control of anther dehiscence process in yellow lupine [ 39 ]. In our study, some genes of the GA signaling pathway were differentially expressed during anther dehiscence period under two conditions.…”
Section: Discussionmentioning
confidence: 99%